Comparative Analysis of Feeding Largemouth Bass (Micropterus salmoides) with Trash Fish and a Compound Diet: Effects on the Growth Performance, Muscle Quality and Health Condition - Yuanhao Yang; Yangfen Xing; Niankun Zhang; Fenggang Li; Xianfang Yan; Mingyue Zhang; Zilin Zhu; Enric Gisbert; Jishu Zhou (Animals)
Two feeding strategies based on the use of trash fish (TF) and an artificial compound feed (ACF) were compared in terms of growth performance, feed efficiency, muscle quality and health status in Micropterus salmoides. For this purpose, fish (128 ± 14 g; n = 102) were divided into two groups and fed with the TF and ACF in triplicate for 90 days. Results showed that the growth performance and condition factor were not affected by the diet, whereas the viscerosomatic and hepatosomatic indexes in the ACF group were higher than in the TF group. The muscle from the TF group had higher levels of 20:5n-3, 22:6n-3, and total n-3 PUFA contents, which resulted in lower thrombogenicity index values. No differences in the amino acid profile were found. Regarding muscle texture properties, only the gumminess and chewiness were significantly lower in the ACF. The use of histological and gene expression biomarkers showed that fish fed TF had a healthier hepatic condition compared to the ACF. The only disadvantage of TF in the current study was the higher values of FCR in comparison to ACF.